2017
DOI: 10.1109/jsen.2017.2665624
|View full text |Cite
|
Sign up to set email alerts
|

An Accurate Wearable Foot Clearance Estimation System: Toward a Real-Time Measurement System

Abstract: Abstract-This work presents an accurate, robust, wearable measurement system for foot clearance estimation along with algorithms to provide a real-time estimate of foot height and orientation. Different configurations of infrared distance meter sensors were used, both alone and in combination with an inertial measurement unit. In order to accurately estimate the foot clearance when in presence of daylight and when the foot orientation changes dynamically during walking, several algorithms were designed based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Dadashi et al [18] found that foot clearance could characterize the risky gait pattern through analyzing the dataset from 1400 participants. Arami et al [19] designed an accurate wearable foot clearance estimation system with infrared distance meter sensors and inertial measurement unit to provide a real-time estimation of foot height and orientation. Several related studies about gait analysis are presented in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Dadashi et al [18] found that foot clearance could characterize the risky gait pattern through analyzing the dataset from 1400 participants. Arami et al [19] designed an accurate wearable foot clearance estimation system with infrared distance meter sensors and inertial measurement unit to provide a real-time estimation of foot height and orientation. Several related studies about gait analysis are presented in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…However, this technology does not allow for direct measurements of the relative position of body segments such as the feet, which are necessary to estimate the base of support or step width variation over time [ 15 ]. Some researchers have combined inertial measurement unit (IMU) with ultrasounds (US), light intensity infrared (IR-LI) and Video camera (VC) sensors [ 16 , 17 , 18 , 19 ]. US sensors estimate a distance by measuring the time required by an ultrasonic wave to travel from the transmitter to the receiver [ 16 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…US sensors estimate a distance by measuring the time required by an ultrasonic wave to travel from the transmitter to the receiver [ 16 , 20 ]. IR-LI sensors determine the distance by measuring the amount of light reflected from an object [ 17 , 18 , 21 ]. VCs have been used to measure the distance from a matrix of infrared LEDs positioned in front of it [ 19 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimation of joint axis and angle estimation using IMU measurements has been shown to be accurate and valid when compared to camera-based motion capture systems [ 53 , 54 ], or compared to magnetic tracking systems [ 55 ]. IMU-based measurement of human kinematics has also been demonstrated with high repeatability and validity, for instance in gait analysis [ 56 , 57 ], and when fused with other sensors [ 58 ], and in 3D joint angle estimation [ 55 ]. Even using a single IMU has been shown to result in accurate motion analysis in studies evaluating rehabilitation exercise performance [ 59 , 60 ].…”
Section: Objective Approachesmentioning
confidence: 99%